Instrumento de avaliação da gestão pública: estudo de caso de uma unidade do Exército Brasileiro - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The road to the development of the public services quality has by his need your avaliation. With this regard, the Federal Government created the Public Management Excellence, wich aims guide the adoption of public organs management excellence pratices. Furthermore, due the mandatory assessment of these management pratices, there is the need to check the accession degree of his most importants management aspect regarding to a management referencial, it was then created the evaluation tool of public management. This research presents an analisys of the management pattern of a public organ situated in souther Rio Grande do Sul in order to the Excellence Model of Public Management and a quantitative avaliation with the Avaliation Tool of Public Management. On Objectives, characterize this work as a exploratory research, because involves a bibliographic survey, interview with people that has pratice experiences with the problem researched and yet an analisys of examples that encourage the understanding. Due the autor of this project be a participant of the studied organ, it ranks this work, on procedures, as a participant research. The methodoligical approach that determines the research consists to realize a documental research in the management plan of the public organ, as well of interviews with high administration. It Checks as results that the institution are in preliminar stage of focus development, the organizational learning happens of isoled form having need of management process integration and, when identify the criteria with most deficiency, it development a Improvement Plan of Management Systems that aims the evolution of Management of the OM in the respectives questions. As future works it suggests an aplication of analog studies to the object of this work in Public agents with the same profile, making possible the benchmarking between intitutions.
Keywords: Engenharia; Engenharia de produção; Modelo de excelência em gestão pública; Instrumento de avaliação da gestão pública; Gestão em serviços públicos; Gestão pública; CNPQ::ENGENHARIAS